Field applicability evaluation of customized central kitchen products in welfare facilities for senior citizens using a mixed-methods design: a pilot study - Lee, Soyoon; Lee, So Jeong; Hwang, Ji-Yun; Chung, Seo-Jin; Park, Ju Yeon; Oh, Jieun; Park, Yoon Jung (Journal of nutrition and health, 2025)
Purpose: Welfare facilities for senior citizens play a critical role in addressing the dietary needs of South Korea’s aging population. However, challenges such as workforce shortages and budget constraints hinder the delivery of effective meal services. Central kitchen (CK) systems aim to standardize services, enhance operational efficiency, and reduce staff workload. This study evaluated the implementation of CK-based meal services in senior welfare facilities, focusing on nutritional management, staff workload, and job satisfaction. Methods: A 2-week intervention was conducted in 2 senior welfare facilities in Seoul, integrating 40 CK products standardized for portion size, texture, sodium, and protein. The mixed-methods design of the study included semi-structured interviews with 5 meal service staff and pre-/post-intervention quantitative assessments of older adults. Of the 55 older adults recruited, 30 participants were included in the final analysis after excluding 18 ineligible adults and 7 with low adherence or incomplete data. The measures assessed included meal satisfaction, physical function (Short Physical Performance Battery [SPPB]), health-related quality of life (5-level EQ-5D version [EQ-5D-5L]), and body weight. Results: The implementation of CK reduced meal preparation time and improved staff job satisfaction and time management. Facility managers reported enhanced inventory control and administrative efficiency. Among meal recipients, meal satisfaction and body weight remained stable (p = 0.136 and 0.559, respectively). While EQ-5D-5L scores showed no significant change, SPPB scores showed a marginally significant improvement in lower-limb function (p = 0.055), with a significant increase in gait speed (p < 0.001). Conclusion: The CK-based meal service model demonstrated feasibility and operational benefits in elderly care settings. While short-term improvements in physical function and quality of life were limited, the intervention effectively reduced staff burden and was not associated with decline in meal quality or satisfaction. These findings suggest the potential of CK systems to scale as a sustainable strategy for improving nutritional management in aging populations. However, further evidence from long-term, controlled studies is needed to substantiate these effects. KCI Citation Count: 0